THE CHILDFREE PHENOMENON: A MACROSOCIOLOGICAL ANALYSIS - T. Bolshunova (Вестник университета)
A life scenario based on childlessness («childfree») is formed and is gaining increasing acceptance in modern society. Its comprehension in the context of postmodernism makes it possible to identify macrosociological reasons for changing family values and reproductive behavior in the modern world. Pluralism, disorganization of moral regulation, decentralization of the individual, loss of gender identity, institutionalization of deviation in the sphere of sexual behavior lead to the transformation of the values of motherhood and parenthood as well as the dysfunctionality of the family. The need for detailed scientific study and understanding of this phenomenon is due to serious socio-demographic consequences.